SPARC Inhibits Epithelial Cell Proliferation in Part through Stimulation of the Transforming Growth Factor-β–Signaling System - Schiemann, Barbara J. (The American Society for Cell Biology, 2003)
Secreted protein, acidic and rich in cysteine (SPARC) is a multifunctional secreted protein that regulates cell–cell and cell–matrix interactions, leading to alterations in cell adhesion, motility, and proliferation. Although SPARC is expressed in epithelial cells, its ability to regulate epithelial cell growth remains largely unknown. We show herein that SPARC strongly inhibited DNA synthesis in transforming growth factor (TGF)-β–sensitive Mv1Lu cells, whereas moderately inhibiting that in TGF-β–insensitive Mv1Lu cells (i.e., R1B cells). Overexpression of dominant-negative Smad3 in Mv1Lu cells, which abrogated growth arrest by TGF-β, also attenuated growth arrest stimulated by SPARC. Moreover, the extracellular calcium-binding domain of SPARC (i.e., SPARC-EC) was sufficient to inhibit Mv1Lu cell proliferation but not that of R1B cells. Similar to TGF-β and thrombospondin-1, treatment of Mv1Lu cells with SPARC or SPARC-EC stimulated Smad2 phosphorylation and Smad2/3 nuclear translocation: the latter response to all agonists was abrogated in R1B cells or by pretreatment of Mv1Lu cells with neutralizing TGF-β antibodies. SPARC also stimulated Smad2 phosphorylation in MB114 endothelial cells but had no effect on bone morphogenetic protein-regulated Smad1 phosphorylation in either Mv1Lu or MB114 cells. Finally, SPARC and SPARC-EC stimulated TGF-β–responsive reporter gene expression through a TGF-β receptor- and Smad2/3-dependent pathway in Mv1Lu cells. Collectively, our findings identify a novel mechanism whereby SPARC inhibits epithelial cell proliferation by selectively commandeering the TGF-β signaling system, doing so through coupling of SPARC-EC to a TGF-β receptor- and Smad2/3-dependent pathway.